Response of forage production to drought in silvopastoral systems in Argentina - Peri, Pablo Luis; Toledo, Santiago; Gandara, Luis; Trinco, Fabio Daniel; Atanasio, Marcos Antonio; Casaubon, Edgardo; Martínez, Natalia; Ledesma, Roxana Ramona; Gómez, Federico Antonio; Lara, Javier Eduardo; Blanco, Lisandro Javier; Carranza, Carlos; et al. (Springer Nature, 2024)
An increase in the frequency and intensity of agricultural and ecological droughts is expected. This study aimed to assess the response of annual forage dry matter production (AFP) to drought in 22 sites across Argentina’s silvopastoral systems (SPS) in native forests and forest plantations and compare it to grasslands and treeless pastures. The AFP was evaluated using a one-way ANOVA with a factorial design, considering the productive system (SPS and grassland/treeless pasture) and hydrological condition year (normal and dry) as factors. Mean AFP ranged from 195 kg DM ha−1 yr−1 to 18,520 kg DM ha−1 yr−1. The results showed that AFP varied according to aridity categories, drought intensity, and forage type (grassland and pastures). Under drought intensity ≤35% (normal year), SPS showed higher AFP than grassland/pastures, while severe drought intensities > 35% (dry year) resulted in the opposite response. The relative response (RR) of AFP in SPSs, compared to grasslands/pastures ranged from -225% to +100%, depending on the site and drought intensity. Principal component analysis of the RR revealed that SPS in semi-arid and semi-humid sites had lower soil carbon and nitrogen concentrations, fewer forage species, and higher AFP values in dry years compared with treeless systems. The information provided in this study may assist in decision-making processes toward more resilient livestock production systems in Argentina.